The Role of microRNA in Cancer Cachexia and Muscle Wasting: A Review Article - Noorwati Sutandyo (Babol University of Medical Sciences, 2021)
Almost half of cancer patients experience cachexia syndrome. Cachexic patients are at risk of increased side effects of chemotherapy, reduced tolerance to chemotherapy drugs, longer duration of treatment period, and decreased quality of life. Cancer cachexia is a multifactorial syndrome. Micro ribonucleic acid (miRNA), a "non-coding RNA", is considered to be a risk factor of cachexia and muscle wasting in cancer patients. miRNA has a role in affecting protein regulation, associated with different inflammatory and disease pathways. miRNA can also affect cytokines or directly change the regulation of metabolism that lead to cachexia. In this review, we want to focus on the pathophysiology to give a better understanding about the role of miRNA in the development of cancer cachexia. Based on various pathways of miRNA in cancer cachexia, it can be a potential target for therapeutic strategies. Improved knowledge about miRNA can give the opportunity to develop new treatment in the management of cancer cachexia.